Effects of adding Huangshui on the yield and quality of strong-flavor Baijiu - PAN Lingling, BAN Shidong, WANG Mei, QIU Shuyi, FENG Xueyu, LUO Mingyou (Zhongguo niangzao)
In order to explore the effect of adding Huangshui on the yield and quality of strong-flavor (Nongxiangxing) Baijiu, using a solid-state fermentation tank with a top that can add Huangshui as the fermentation vessel, the physical and chemical indicators of the fermented grains and the content of main flavor substances were compared and analyzed during the fermentation process in the experiment tank, the control tank (without Huangshui) and the pits (without Huangshui). After fermentation, the yield and quality of the base liquor were compared. The results showed that during the fermentation process, the change trends of moisture, starch, reducing sugar, acidity, alcohol content, main flavor substances in the experimental tank, control tank and pit fermented grains were basically the same. 14-50 d was the high production period of flavor substances, and 35-50 d was the synthesis period of important ester substances. After fermentation, the liquor yield of the experimental tank was increased by 1.4% and 6.5% compared with the control tank and pit tank, respectively. The sensory evaluation of the second-stage base wine in the experimental tank was better than that in the control tank and pit tank. The sensory evaluation of the second-stage base liquor in the experimental tank was better than that in the control tank and pit tank. Its content of main flavor components was better than that in the control tank and had little difference from the pit. Among them, the second-stage base liquor contains ethyl hexanoate, ethyl acetate, ethyl lactate, ethyl butyrate, acetic acid and butyric acid was 9.3%, 7.8%, 47.2%, 2.7%, 7.7%, 10.6% higher than the control tank, respectively. It could be seen that adding Huangshui to fermentation outside the pit could improve the yield and quality of strong-flavor Baijiu.